Dom Brandão, o profeta do povo de Deus do baixo São Francisco - Nascimento Filho, Isaías Carlos (2012)
This dissertation analyzes, as a phenomenon of the Brazilian religious field, the ecclesiastical trajectory and the pastoral action of Dom José Brandão de Castro, in the period from 1960 to 1987, regarding the peasants, natives, landless workers, fishermen and quilombolas, who form the poorest population segment of the State of Sergipe, emphasizing his option for the poor who were organized in the Ecclesiastic Base Communities (EBCs),considering the Theology of Liberation, and the consequences which followed his option. The CEHILA method was the one used in the historiographical reconstruction, because of its double utility: as an historical methodology specially designed to rescue the history of those who normally have no voice, and as theological stance, since this is the story of the faith journey of an excluded people who after finally finding a pastor that listens to them, organized themselves in a process of liberation. The researches rebuilt part of the paths taken by Dom José Brandão, starting with his family, through his education, priestly and Episcopal ministry as a Redemptorist missionary, until his renunciation of the position of Bishop of Propriá. They portray how he improved his sensitivity towards the poor, moving progressively from an affective-assistance -based attitude to an affective-libertarian attitude, whose consistency made him pay a heavy price: the forced renunciation. The testimonies reveal that he left a legacy of liberation that remains in the memory, the expressions of faith and in the attitudes of several communities and organized groups in the Lower São Francisco, until the present day.